RANCANG BANGUN SISTEM INFORMASI KOLAM PEMANCINGAN KLEKAK BUNDA DENGAN UPDATE DATA SISTEM MENGGUNAKAN APLIKASI ANDROID BERBASIS IOT - herda tantri; Mayesa Nur Akhad; Aan Febriansyah; Irwan Irwan (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
The fishing pond business is currently a trend, so good management is needed. One important aspect is the existence of an information system for the schedule and duration of fishing time. An IoT-based information system is a device that is used as an information delivery media. This information system uses IoT-based wireless communication which is controlled by via Android. The purpose of this research is to design and develop an information system that is integrated with Android in this fishing pond business so that the delivery of information is more efficient. The methodology in this research used primary data collection and literature study. Hardware manufacture is done by selecting the type and color of the Dot Matrix. Software development is carried out using the Arduino Uno microcontroller and the PA 2022 application as a data control system. The result of this research is an information system that is efficient and easy to operate and has an accurate fishing duration. This information system is the result of the development of an existing information system.